2020
DOI: 10.3389/fmicb.2020.01588
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Genome Sequencing of Five Novel Bacteriophages From the Rumen Active Against Butyrivibrio fibrisolvens

Abstract: Although the prokaryotic communities of the rumen microbiome are being uncovered through genome sequencing, little is known about the resident viral populations. Whilst temperate phages can be predicted as integrated prophages when analyzing bacterial and archaeal genomes, the genetics underpinning lytic phages remain poorly characterized. To the five genomes of bacteriophages isolated from rumen-associated samples sequenced and analyzed previously, this study adds a further five novel genomes and predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Also, sequencing of DNA from isolated viruses is a powerful strategy to obtain the genomic information, functional prediction, and a better understanding of phages and its interaction with bacteria. Together, Gilbert et al (2017) and Friedersdorff et al (2020) , reported the entire genome of 10 ruminal phages. According to Friedersdorff et al (2020) , sequenced phages were in a lytic life cycle; however, the functional genomic analysis enabled to infer that some of the phages had lysogeny-associated genes, which suggest that some of these phages could have a temperate life cycle as well.…”
Section: Use Of Technologymentioning
confidence: 98%
See 3 more Smart Citations
“…Also, sequencing of DNA from isolated viruses is a powerful strategy to obtain the genomic information, functional prediction, and a better understanding of phages and its interaction with bacteria. Together, Gilbert et al (2017) and Friedersdorff et al (2020) , reported the entire genome of 10 ruminal phages. According to Friedersdorff et al (2020) , sequenced phages were in a lytic life cycle; however, the functional genomic analysis enabled to infer that some of the phages had lysogeny-associated genes, which suggest that some of these phages could have a temperate life cycle as well.…”
Section: Use Of Technologymentioning
confidence: 98%
“…Together, Gilbert et al (2017) and Friedersdorff et al (2020) , reported the entire genome of 10 ruminal phages. According to Friedersdorff et al (2020) , sequenced phages were in a lytic life cycle; however, the functional genomic analysis enabled to infer that some of the phages had lysogeny-associated genes, which suggest that some of these phages could have a temperate life cycle as well. Gilbert et al (2017) , provided insights on how lytic phages interact with the host bacteria in the rumen environment.…”
Section: Use Of Technologymentioning
confidence: 98%
See 2 more Smart Citations
“…For example, phages have been used to control bacterial infections in dairy cattle with mastitis, which is a common and costly disease in the dairy industry [24]. Despite tremendous success in identifying viruses from various environmental sources such as the ruminants rumen [25][26][27][28][29][30][31],…”
Section: Introductionmentioning
confidence: 99%